Soil pH and Electrical Conductivity: A County Extension Soil Laboratory Manual - Rao Mylavarapu; Jamin Bergeron; Nancy Wilkinson; E. A. Hanlon (EDIS)
This is a minor revision with new authors.  Originally published April 1993 by E.A. Hanlon. This manual has been designed as a reference source for UF/IFAS Extension county offices offering soil pH and/ or electrical conductivity tests to their clients. This manual if followed, will assist county faculty in assuring that these laboratory measurements are done correctly with high quality assurance. https://edis.ifas.ufl.edu/ss118